2013
DOI: 10.1002/jbm.b.32904
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wear, wear particles, and reduced inflammatory potential of vitamin E ultrahigh‐molecular‐weight polyethylene for use in total joint replacement

Abstract: Vitamin E (VE) has been added to ultrahigh-molecular-weight polyethylene (UHMWPE) acetabular cups and tibial trays primarily to reduce oxidative damage to the polymer. The aim of this study was to investigate the relative wear rates of UHMWPE-containing VE compared with virgin UHMWPE. The ability of VE to reduce the amount of inflammatory cytokines produced from stimulated peripheral blood mononuclear cells (PBMNCs) was also investigated. Stimulation was achieved by exposure of PBMNCs to either lipoplysacchari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Crosslinking of UHMWPE reduces the wear and risk of osteolysis efficiently [21][22][23][24]. The addition of vitamin E to UHMWPE not only improves oxidative stability but also reduces the biologic activity of the wear particles [25,26]. The latter advantage is however controversial [27].…”
Section: Discussionmentioning
confidence: 99%
“…Crosslinking of UHMWPE reduces the wear and risk of osteolysis efficiently [21][22][23][24]. The addition of vitamin E to UHMWPE not only improves oxidative stability but also reduces the biologic activity of the wear particles [25,26]. The latter advantage is however controversial [27].…”
Section: Discussionmentioning
confidence: 99%
“…1,9,20 In particular, it has been demonstrated that oxidative degradation of UHMWPE gamma-sterilized in air increased its wear while decreasing mechanical strength, constituting the main cause of the dramatic implant failures occurred in the last years. [21][22][23] As a consequence, many efforts have been made to improve UHMWPE quality and performance, for example through the reduction or elimination of the oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…7,20,23,24 VE, a free radical scavenger and well established biological antioxidant, prevented oxidation and delamination and had a favorable long-term effect on fatigue performance of the UHMWPE, increasing the resistance to fatigue cracks associated with oxidation without negatively altering the biocompatibility of the implant. 20,24 Moreover, it has been shown that VE when added to UHMWPE does not have any cytotoxic effects and acts as an effective anti-inflammatory. 9 In this study we quantified the adhesion of well-characterized biofilm producing collection strains of S. aureus and E. coli, as pathogens mostly associated with periprosthetic infection, to standard UHMWPE, to VE blended UHMWPE and to oxidized UHMWPE taking into account that for a given material surface, different bacterial species and strains adhere differently since different species and strains have different physicochemical characteristics: 14,15 slime producer S. epidermidis and S. aureus have a comparatively thicker and more rigid peptidoglycan layer respect to a fimbriae producer E. coli, and extensive contact of their external cell-structure with the implant surface may be quite different.…”
Section: Discussionmentioning
confidence: 99%
“…The VE stabilization of UHMWPE has been recently proposed to improve oxidation resistance while maintaining wear resistance and fatigue strength. 7,20,23,24 VE, a free radical scavenger and well established biological antioxidant, prevented oxidation and delamination and had a favorable long-term effect on fatigue performance of the UHMWPE, increasing the resistance to fatigue cracks associated with oxidation without negatively altering the biocompatibility of the implant. 20,24 Moreover, it has been shown that VE when added to UHMWPE does not have any cytotoxic effects and acts as an effective anti-inflammatory.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a significant decreased bacterial adhesion was registered for both bacteria on VE-PE, in comparison with that observed on PE, within 48h of observation ( Figure 3 A and B), underlying the role of VE, probably related to its well established antioxidant properties. 9,20 The mechanism by which VE may affect the bacterial adherence to UHMWPE it is currently unknown, even if potential effects of VE on infection are currently investigated. 25 The CA measurements showed no significant variations in hydrophilicity between PE and VE-PE suggesting that other, concurrent factors must be involved in the different bacterial adhesion.…”
Section: S Epidermidismentioning
confidence: 99%